2015
DOI: 10.1038/labinvest.2014.138
|View full text |Cite
|
Sign up to set email alerts
|

Anterior gradient 2 downregulation in a subset of pancreatic ductal adenocarcinoma is a prognostic factor indicative of epithelial–mesenchymal transition

Abstract: Anterior gradient 2 (AGR2), a member of the protein disulfide isomerase family, has been implicated in various cancers including pancreatic ductal adenocarcinoma (PDAC) and is known to promote cancer progression. However, the prognostic value of AGR2 expression and the interaction with epithelial-mesenchymal transition (EMT) remain unclear. We investigated the clinical significance of AGR2 and EMT markers in PDAC patients by immunohistochemical analyses. Although AGR2 expression was not observed in normal panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…Moreover, although ID2 has been previously associated with EMT and shown to suppress the SMAD pathway [39][40][41], decreasing of ID2 expression by TGF-b1 stimulation was confirmed by RNA-Seq and real-time RT-PCR in the present study. Previously, a role for AGR2 in EMT was investigated [42][43][44]. We also confirmed that AGR2 expression was down-regulated by TGF-b1.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, although ID2 has been previously associated with EMT and shown to suppress the SMAD pathway [39][40][41], decreasing of ID2 expression by TGF-b1 stimulation was confirmed by RNA-Seq and real-time RT-PCR in the present study. Previously, a role for AGR2 in EMT was investigated [42][43][44]. We also confirmed that AGR2 expression was down-regulated by TGF-b1.…”
Section: Discussionsupporting
confidence: 79%
“…In tumorigenesis, AGR2 plays an important role by activating survival and metastasis pathways by interacting with cyclin D1, cathepsin B, D, Myc, p‐Src, and EGFR and by blocking cell death inhibiting p53 function. The overexpression of AGR2 was observed in several tumor types, which supports the hypothesis of AGR2 be an oncogene, but the downregulation of this gene also was observed in prostate tumors, ovarian, colorectal, and pancreas …”
Section: Introductionsupporting
confidence: 76%
“…Nevertheless, original studies of AGR2 show that this protein has an important function in the preservation of cellular homeostasis, by promoting the differentiation of secretory epithelial cells . Downregulation of AGR2 seems to be related to tumor progression of tumors originating in secretory organs . Thus, hypothetically, in the early stage of the tumor, increased AGR2 expression could activate proliferative mechanisms, such as increased cyclin D1, but with tumor progression, the reduction in AGR2 could activate mechanisms of invasion and metastasis by reducing adhesion molecules .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, K-ras(G12D)/Smad4(lox/lox) mice that are heterozygous for agr2 are attenuated in initiation and progression to pancreatic ductal cell carcinoma [74]. Consistent with this study, secretion of TGF-␤ from pancreatic stellate cells might reduce agr2 expression in pancreatic ductal adenocarcinoma [75]. Another cancer type where the TGF-␤/AGR2 axis might play a role in carcinogenesis is oesophageal adenocarcinoma [68].…”
Section: Agr2 Gene and Protein Expression In Relation To Cancer Cell supporting
confidence: 80%